Deteksi Hoaks Dan Ujaran Kebencian Masyarakat Daerah Terpencil Desa Bakaru Kabupaten Pinrang - Sari Hidayati; Nahrul Hayat; Mifda Hilmiyah; Suhardi Suhardi; Sunandar Sunandar (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2024)
Hoaxes as fake news trigger various debates and misunderstandings in society. The purpose of this research is to detect the receptive level of the Bakaru Village community who are new users of internet services. Before the community is easily influenced by false discourses that are difficult to control, the community must have the insight that not all writings or utterances on the internet, especially social media, are facts. This research method was carried out in conjunction with community service in Bakaru Village, namely in the Literacy Village activity. The results of this research are the level of trust of the Bakaru Village community in responding to hoaxes and introducing insights into hate speech. Despite being an underdeveloped and remote village, based on the results of the review, the Bakaru Village community has a foundation of belief not to easily believe in every new thing without confirmation from the hoax victim. Hoax news is not easily spread in this village because of the difficulty in interacting through social media, as well as hate speech that is not easily produced because the forum for expressing opinions on news is only through direct interaction.